2019
DOI: 10.1155/2019/3291628
|View full text |Cite
|
Sign up to set email alerts
|

Is Pectus Excavatum a Risk Factor for Spontaneous Pneumothorax? “Haller Index Measurements in Patients with Primary Spontaneous Pneumothorax”

Abstract: Aim. In this study, we aimed to retrospectively investigate whether pectus excavatum (PE) is a risk factor for the development of primary spontaneous pneumothorax (PSP) and to determine its role in the etiology of the disease. Materials and Methods. Chest-computed tomography (CT) of the patients who were treated for spontaneous pneumothorax between January 2015 and December 2017 in our clinic was examined, and their Haller indices were measured (group I). The patients in the control group who underwent chest C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
4
1
2
Order By: Relevance
“…Shiiya and colleagues reported that in patients with apical pleural holes the chest wall flatness was not as severe as that in subjects without pleural holes. This chest wall feature in patients with pleural holes still seems flatter in respect to normal controls reported in other studies, although the chest wall method of measurement was slightly different from Shiiya’s group ( 19 , 20 ). In Shiiya et al ’s opinion, these features suggest that subjects with apical pleural holes may have some specific findings that leads to pneumothorax, which are different from other subjects with primary spontaneous pneumothorax.…”
contrasting
confidence: 69%
“…Shiiya and colleagues reported that in patients with apical pleural holes the chest wall flatness was not as severe as that in subjects without pleural holes. This chest wall feature in patients with pleural holes still seems flatter in respect to normal controls reported in other studies, although the chest wall method of measurement was slightly different from Shiiya’s group ( 19 , 20 ). In Shiiya et al ’s opinion, these features suggest that subjects with apical pleural holes may have some specific findings that leads to pneumothorax, which are different from other subjects with primary spontaneous pneumothorax.…”
contrasting
confidence: 69%
“…Our group reported a higher incidence of PSP in PE patients in Taiwan, with a 7.83-fold increased risk [8]. Kılıc ¸gu ¨n et al [9] published a finding of a higher mean HI in PSP patients than in the control group (2.41 vs. 2.09, p = 0.006). In our data from 2011 to 2014, we also found a higher average HI of 2.81 among 304 PSP patients.…”
Section: Introductionmentioning
confidence: 79%
“…Patients with PE were reported to have a significantly higher cumulative incidence of PSP that was approximately twice that (0.36% vs. 0.15%; hazard ratio 7.83 and p = 0.002) of a control group ( 10 ). Additionally, Kılıçgün et al ( 11 ) found that patients with PSP had a significantly higher mean HI (2.41 vs. 2.09, p = 0.006) compared to those in the control group. Moreover, Peters et al ( 12 ) reported that PSP was associated with a longer and flatter chest shape, and Park et al ( 13 ) showed that PSP patients had anteroposteriorly flatter, laterally narrower, and craniocaudally taller thoraxes.…”
Section: Discussionmentioning
confidence: 97%